1997
DOI: 10.1103/physrevb.55.14035
|View full text |Cite
|
Sign up to set email alerts
|

In situ neutron-reflectometry measurements of hydrogen and deuterium absorption in a Pd/Nb/Pd layered film

Abstract: We present in situ neutron-reflectivity measurements of the hydrogen and deuterium absorption from the gas phase in a Pd/Nb/Pd thin film multilayer. Hydrogen and deuterium were both preferentially absorbed into the Nb layer at room temperature and at a pressure of 10 Torr. Genetic algorithm fits to the specular data indicate concentrations of approximately 0.71 ͓H͔/͓Nb͔ and 0.51 ͓D͔/͓Nb͔, placing the Nb well into the ␤ phase ͑or an ␣Ј-like phase͒. ͓S0163-1829͑97͒07021-5͔

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In contrast, the scattering length for neutrons varies randomly from element to element, and, as a consequence, hydrogen in a given material usually scatters as strongly, or sometimes stronger, than the absorbing medium. The fact that both hydrogen and deuterium atoms strongly scatter neutrons opens up the opportunity for isotope contrast variation [39]. These combined properties make neutron scattering a unique tool to identify the location and concentration of hydrogen in hydride materials.…”
Section: Introduction: Hydrogen Absorption In Metals-bulk Versus Thinmentioning
confidence: 99%
“…In contrast, the scattering length for neutrons varies randomly from element to element, and, as a consequence, hydrogen in a given material usually scatters as strongly, or sometimes stronger, than the absorbing medium. The fact that both hydrogen and deuterium atoms strongly scatter neutrons opens up the opportunity for isotope contrast variation [39]. These combined properties make neutron scattering a unique tool to identify the location and concentration of hydrogen in hydride materials.…”
Section: Introduction: Hydrogen Absorption In Metals-bulk Versus Thinmentioning
confidence: 99%
“…Later, Munter et al showed how deuterium absorption could be monitored in-situ during loading experiments on thin Pd films 9,10 . More recently, a series of studies has been published by Fritzche et al, showing how NR can be used to investigate the thermodynamics of hydrogen uptake process in Pd-capped metal alloy films [11][12][13][14][15] .…”
mentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28][29][30] This ability is empowered by the high contrast between hydrogen isotopes (hydrogen and deuterium) which can be used to precisely probe, non-destructively, the amount of hydrogen penetrating into the metal and any surface films. The fact that NR can be carried out in situ by applying a controlled electrochemical condition adds a new dimension to the study of hydrogen transport through the oxide and metal films, and of their corrosion resistance.…”
mentioning
confidence: 99%